Wage and Public Debt Indexation - Guidotti, Pablo (IMF Working Papers; Working Paper ;, 1992)
This paper examines the relationship between the degree of wage indexation chosen by private agents and the degree of indexation of the public debt. It is shown that the government is likely to respond to an increase in the degree of wage indexation by increasing the portion of the public debt that is indexed. By contrast, the effect of an increase in public debt indexation on the degree of wage indexation is ambiguous. In equilibrium, depending on the sources of shocks to the economy, the degree of wage indexation may be positively or negatively related to that of debt indexation. This relationship is analyzed both in situations where the policymakers are able to precommit policies and in those where precommitment is not possible.